Chyle leak following pancreatico‐duodenectomy: a tertiary hepatopancreaticobiliary unit's experience and a proposed management algorithm. Issue 3 (18th January 2021) - Russell, Thomas; Tanase, Andrei; Bowles, Matthew; Briggs, Christopher; Kanwar, Aditya; Stell, David; Aroori, Somaiah
Abstract: Background: Chyle leak (CL) is an uncommon complication of pancreatico‐duodenectomy (PD). Its incidence, risk factors, and effect on prognosis are not well described and optimum management remains debated. This study aims to calculate incidence of CL following PD and identify risk factors. Following a literature review, we have proposed a management algorithm. Methods: This is a retrospective review of all patients who underwent PD between January 2006 and April 2020 at a tertiary hepatopancreaticobiliary unit in the UK. The following data were obtained: age, gender, American Society of Anesthesiologists grade, body mass index, co‐morbidities, duration of surgery, tumour histology, length of stay and mortality. Results: A total of 560 patients were included. Seventeen developed CL (3.04%). Median age was 64 years (range 50–81). Sixteen (94.1%) patients still had their surgical drain in at the time of CL diagnosis. One (5.9%) did not and had free intra‐abdominal fluid on computed tomography; a diagnosis was made after an ultrasound‐guided drain had been inserted. CL patients were more likely to have higher body mass index (mean 30.5 kg/m 2 (range 17–43) versus 26.7 kg/m 2 (22–38)) ( P = 0.02) and longer duration of operation (mean 6.2 h (range 4.3–9.0) versus 5.6 (3.0–11.0)) ( P = 0.03). All cases of CL resolved without operative intervention. CL did not affect length of stay (median 10 days (range 4–41) versus 11 (4–34)). Conclusions: In our series, 3.04% of patients who underwent PD developed CL. No patients required a return to theatre, and none had CL recurrence. Abstract : This study aims to calculate the incidence of chyle leak (CL) following pancreatico‐duodenectomy, identify risk factors, and propose a simple management algorithm. A total of 560 patients were included and 17 (3.04%) developed CL. Patients with CL had significantly higher body mass index and longer duration of operation. All patients were successfully managed without a return to theatre.